Laparoscopic sacrohysteropexy: the Pilsner modification - Kalis, Vladimir; Rusavy, Zdenek; Ismail, Khaled M (International urogynecology journal, 2020)
INTRODUCTION AND HYPOTHESIS: Laparoscopic sacrocolpopexy is the preferred contemporary procedure for the surgical management of a significant apical pelvic organ prolapse. In the presence of a uterus it is possible for the patient to have subtotal hysterectomy and cervicopexy, total hysterectomy with colpopexy or uterine conservation and hysteropexy. However, hysteropexy seems to be associated with a higher risk of anterior compartment failure compared with cervicopexy or colpopexy. It is not uncommon for an asymmetrically large anterior compartment defect to co-exist with a symptomatic apical pelvic organ prolapse. In a cervicopexy or colpopexy, this asymmetry can be balanced by creating a de novo vaginal apex from the superior part of the anterior vaginal wall. However in a hysteropexy the attachment of the base of the anterior mesh to the vagina and cervical isthmus limits the ability to do this. METHODS: In this video we present a solution where the shape of the posterior mesh is modified to include two horizontal arms that are passed through openings in the broad ligament and attached to the cervical isthmus anteriorly. RESULTS: This frees the anterior Y-shaped mesh to be fixed to the anterior vaginal wall only and hence provides the required tension to create the de novo apex. CONCLUSION: Prior to wide adoption, this technique should be further investigated in the context of robustly designed comparative studies.
Keywords: výsledek terapie; Anterior compartment; Sacrohysteropexy; prolaps pánevních orgánů; Surgical Mesh; gynekologické chirurgické výkony; chirurgické síťky; Mesh; Gynecologic Surgical Procedures; laparoskopie; Uterus; Pelvic Organ Prolapse; uterus; Treatment Outcome; Cystocele; lidé; ženské pohlaví; Humans; Laparoscopy; Vagina; Female; vagina; Prolapse